Sprint Interval Training and Continuous Aerobic Exercise Training Have Similar Effects on Exercise Motivation and Affective Responses to Exercise in Patients With Major Depressive Disorders: A Randomized Controlled Trial - Gerber, Markus; Minghetti, Alice; Beck, Johannes; Zahner, Lukas; Donath, Lars (Frontiers in Psychiatry, 2018)
Background: Sprint interval training (SIT) has become increasingly popular, and is seen as a promising exercise strategy to increase fitness in healthy people. Nevertheless, some scholars doubt the appropriateness of a SIT training protocol for largely physically inactive populations. SIT might be too arduous, and therefore contribute to feelings of incompetence, failure, and lower self-esteem, which may undermine participants’ exercise motivation. Therefore, we examined whether participation in twelve SIT sessions would lead to different changes in self-determined motivation, affective responses to exercise, cardiorespiratory fitness, physical activity, and depressive symptom severity compared to aerobic exercise training (CAT) in a sample of patients with major depressive disorders (MDD). Methods: Two groups of 25 patients (39 women, 11 men) with unipolar depression were randomly assigned to the SIT or CAT condition (M=36.4 years, SD=11.3). Data were assessed at baseline and post-intervention (three weekly 35-min sessions of SIT/CAT over a 4-week period). Self-determined exercise motivation was assessed with a 12-item self-rating questionnaire, affective valence was assessed in each session, prior, during, and after the exercise training using the Feeling Scale (FS). Cardiovascular fitness was measured with a maximal bicycle ergometer test, self-perceived fitness with a 1-item rating scale, physical activity with the International Physical Activity Questionnaire (IPAQ-SF), and depressive symptom severity with the Beck Depression Inventory II. Results: The SIT and CAT groups did not differ with regard to their changes in self-determined motivation from baseline to post-intervention. Participants in the SIT and CAT group showed similar (positive) affective responses during and after the training sessions. Cardiorespiratory fitness, self-perceived fitness and depressive symptom severity similarly improved in the SIT and CAT group. Finally, significant increases were observed in self-reported physical activity from baseline to post-intervention. However, these increases were larger in the CAT compared to the SIT group. Conclusion: From a motivational point of view, SIT seems just as suited as CAT in the treatment of patients with MDD. This is a promising finding because according to self-determination theory, it seems advantageous for patients to choose between different exercise therapy regimes, and for their preferences with regard to exercise-type and intensity to be considered.